Engaging locals in rural areas: value correspondence in placemaking through mobile augmented reality. Issue 3 (3rd July 2021) - Her, Jiun-Jhy
ABSTRACT: This research proposes value correspondence, which posits that the value shared in correspondence between stakeholders is essential for the development of placemaking in rural areas. By investigating location-based media; particularly mobile augmented reality (MAR) apps aimed at both reviving local tourism in rural townships and soliciting opinions from major stakeholders, the author has determined that local residents play a vital role in the placemaking process. However, research in this field has often ignored local residents and instead focused on tourists' perceptions and augmented reality technology. Various MAR apps have been designed as forms of self-service technology that benefits tourists but, to some extent, also hinders dialog between tourists and locals; this results in value noncorrespondence, which may lead to the failure of placemaking. Thus, the author advocates that more attention should be paid to how locals can generate value in correspondence with other stakeholders via the use of MAR.